TANTANGAN DAN STRATEGI PELAKSANAAN INDONESIA-AUSTRALIA COMPREHENSIVE ECONOMIC PARTNERSHIP AGREEMENT (IA-CEPA) - Yafet Yosafet W. Rissy (Universitas Kristen Satya Wacana, 2021)
The Indonesia-Australia Comprehensive Economic Partnership Agreement (IA CEPA) has been entered into force on July 5, 2020. This article examines the objectives and substance of the IA-CEPA, scrutinizes the challenges of the IA-CEPA free trade agreement model, and offers several strategies for Indonesia in implementing the IA-CEPA. In general, the objectives of the IA-CEPA are to promote the enhancement of trade, investment, economic cooperation, the smooth flow of goods, services, and people, including reducing tariffs to zero (0)% and eliminating other non-tariff barriers. On the Indonesian side, however, there are a number of fundamental challenges that need to be resolved in order to gain the maximum benefits. One of the major challenges facing Indonesia today is the large trade deficit towards Australia. To overcome this issue, a number of strategies need to be considered such as implementing the economic powerhouse concept, increasing skilled workers, and providing high-quality vocational education.